Paint Shop Pro 8 for Dummies - Kay, David (Wiley Publishing, 2011)
Published in conjunction with the new release of Paint Shop Pro, this book walks readers through image-editing fundamentals as well as more advanced graphics and animation tools Shows photography and animation hobbyists how to create quality, professional-looking graphics Discusses painting, spraying, retouching photos, adding artistic effects, layering, masking layers, adjusting color, moving, reshaping, copying, and printing images Also examines how to create Web images and animated graphics with Jasc's Animation Shop Author has written more than a dozen technology books